Comparative Raman spectroscopy of magnetic topological material EuCd2X2 (X = P, As). (1st June 2022) - Du, Yuhan; Chen, Ju; Wu, Wenbin; Shi, Zeping; Meng, Xianghao; Zhang, Cheng; Gong, Shijing; Chu, Junhao; Yuan, Xiang
Abstract: EuCd2 X2 (X = P, As) is a new class of magnetic topological materials discovered recently. The electronic structure and the band topology are intimately coupled with its magnetism, giving rise to interesting properties such as spin fluctuation and colossal magnetoresistance. Phonon excitation can contribute to the quasi-particle response of the topological matters through spin-lattice and electron–phonon coupling. However, the phonon properties of this material family remain unexplored. Here we report a comparative study of Raman-active vibration modes in EuCd2 X2 (X = P, As) by means of angle-resolved, temperature-resolved, and magnetic-field-resolved Raman spectroscopy together with the first-principle calculations and Raman tensor analysis. The phonon properties can be tuned by chemical potential and temperature within the material family. All the phonon modes are softened with increased chemical pressure by replacing P with As. Angle-resolved polarized Raman spectroscopy reveals the configuration-sensitive Raman activity and the isotropic intensity response. In addition, the magneto-Raman spectrum indicates the stability of Raman-active vibration modes against the magnetic field at room temperature. Our work sheds light on the phonon dynamics of magnetic topological matters, which are potentially coupled with the topological charge and spin excitation.